PRINCIPLES OF MUTUAL TRUST IN CRIMINAL JUDICIAL PROCEDURE IN THE EUROPEAN UNION: THE CASE OF ARAÑOS AND CALDARAR - SNIGUR, MYKOLA (Ehrlich’s Journal, 2025)
The principles studied in this paper guide the judgments of the Court of Justice of the European Union (then applied to specific cases by national judges) and determine the very implementation of the European legal order. The best way to understand the contemporary meaning and implications of such principles is through the principled case law of the Court of Justice of the European Union, which is so qualified because it speaks to a specific case when considering the application of the principles. An assessment of European jurisprudence shows that principles are (and should be) the rules on which decisions concerning EU law are based, which is why it is urgent to understand them in order to apply them correctly, ensuring the unity of the European legal order. The Caldararu – Aranyosi judgment is characterised by a constant search for a balance between the effectiveness of the European Arrest Warrant and the concern for respect for fundamental rights. By acknowledging the possibility of taking into account the risk to fundamental rights and enshrining the possibility of a final refusal to execute a European arrest warrant, the CJEU imposes certain limitations on mutual trust. In its rationale, the Court emphasises the fundamental importance of the principle of mutual trust, recognising that limitations may be permitted in exceptional circumstances. It also points to the absolute nature of the prohibition of inhuman and degrading treatment, which means that no derogation is permitted. Thus, if there is ‘evidence of a real risk of inhuman or degrading treatment of persons detained in the issuing Member State’, the executing judicial authority is obliged to assess the existence of the risk. To do so, it must verify the reality of the deficiencies and assess, ‘specifically and precisely, whether there are substantial grounds for believing that the person concerned would be exposed to such a risk due to the conditions of detention provided for in the issuing Member State’.